Estrogen improves the hyperdynamic circulation and hyporeactivity of mesenteric arteries by alleviating oxidative stress in partial portal vein ligated rats - Zhang, Bin (Baishideng Publishing Group Co., Limited, 2013)
AIM: To evaluate the effects of estrogen (E2) on systemic and splanchnic hyperdynamic circulation in portal hypertensive rats. METHODS: Fifty castrated female Sprague-Dawley rats were divided into five groups: sham operation (SO), partial portal vein ligation (PPVL) + placebo (PLAC), PPVL + E2, PPVL + ICI and PPVL + E2 + ICI. Hemodynamic measurements were performed using ultrasonography. Mesenteric arteriole contractility in response to norepinephrine was determined using a vessel perfusion system. Oxidative stress in the mesenteric artery was investigated by in situ detection of the superoxide anion (O(2)•(−)) and hydrogen peroxide (H(2)O(2)) concentrations. RESULTS: Treatment with E2 resulted in a significant decrease of portal pressure (P < 0.01) and portal venous inflow (P < 0.05), and higher systemic vascular resistance (P < 0.05) and splanchnic arteriolar resistance (P < 0.01) in PPVL + E2 rats compared to PPVL + PLAC rats. In the mesenteric arterioles of PPVL + E2 rats, the dose-response curve was shifted left, and the EC(50) was decreased (P < 0.01). E2 reduced O(2)•(−) production and H(2)O(2) concentration in the mesenteric artery. However, ICI182, 780 reversed the beneficial effects of E2, therefore, the systemic and splanchnic hyperdynamic circulation were more deteriorated in ICI182, 780-treated rats. CONCLUSION: Treatment with estrogen improved the systemic and splanchnic hyperdynamic circulation in PPVL rats, in part due to the alleviation of oxidative stress.